2020
DOI: 10.1152/ajpcell.00192.2019
|View full text |Cite
|
Sign up to set email alerts
|

Contributing mechanisms underlying desensitization of cholecystokinin-induced activation of primary nodose ganglia neurons

Abstract: Cholecystokinin (CCK) is a gut-derived peptide that potently promotes satiety and facilitates gastric function in part by activating G protein-coupled CCK1 receptors on primary vagal afferent neurons. CCK signaling is dynamic and rapidly desensitizes, due to decreases in either receptor function and the resulting signal cascade, ion channel effectors, or both. Here we report a decay-time analytical approach using fluorescent calcium imaging that relates peak and steady-state calcium responses in dissociated va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Previous studies of VANs involving patch-clamp or calcium imaging interrogation were primarily performed in acute settings (less than 24 h in vitro [ 15 , 22 , 24 , 26 , 31 , 32 ]). Extracellular recordings, on the other hand, require longer culture durations for the cells to attach to or near the electrodes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies of VANs involving patch-clamp or calcium imaging interrogation were primarily performed in acute settings (less than 24 h in vitro [ 15 , 22 , 24 , 26 , 31 , 32 ]). Extracellular recordings, on the other hand, require longer culture durations for the cells to attach to or near the electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the surface coatings, two media types were also compared. A common media composition used for acute cultures of VANs is DMEM supplemented with 10% FBS (referred to as serum-based media) [ 15 , 22 , 24 , 26 ]. We hypothesized that a more specialized neuronal culture medium would better sustain neuronal cell viability and function in the non-acute cultures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may align with prior studies demonstrating that circulating BAs mediate release of cholecystokinin (CCK), and that CCK signaling is dynamic and rapidly desensitizes. 66 In contrast, perfusion of SCFAs into the SI lumen increased afferent vagal nerve activity following a latency period in an FFAR2-dependent manner ( Figure 3D-F ), suggesting indirect activation of FFAR2-expressing epithelial cells and subsequent GLP-1 release. 67 Finally, we found that microbiome-dependent 3IS in the small intestine elicited sustained afferent vagal nerve activity in a TRPA1-dependent manner ( Figure 3G-I ).…”
Section: Discussionmentioning
confidence: 91%
“…Physiological CCK-AR stimulation induces exocrine pancreatic enzyme secretion and endocrine pancreatic polypeptide secretion 18 . CCK-AR limits acid secretion by releasing pepsin from primary gastric cells and somatic statin from gastric mucus D cells 19 . A decrease in small bowel passage time and a rise in colonic passage time are all caused by CCK-AR on smooth muscle cells, and the second is the anterior nucleus accumbens CCK-BR inhibits dopamine release.…”
Section: Introductionmentioning
confidence: 99%